Is South Africa's headquarter regime successful and does it go against national legislation? Are rewards from a customer loyalty programme capital or revenue in nature? - Mohamed, Ismail (Department of Commercial Law, 2016)
Research paper 1. (International tax) Is South Africa's headquarter regime successful and does it go against national legislation. This research paper discusses how South Africa has changed its legislation to become the Gateway of investment into Africa. It addresses the prior barriers previously faced by investors in South Africa and Africa as well as changes to legislation to accommodate this problem. The current criteria tin qualifying as a headquarter company is addressed in terms of Section 80 A of the Income Tax Act, which also addresses the draw backs and restrictions which as a result South Africa has not received any applications by companies in becoming a headquarter company. A comparison is drawn between South Africa's headquarter regime versus a well - known popular tax haven country namely Mauritius. A comparison is performed on both the qualification in becoming headquarter companies as well as the tax benefits thereto which encourage investment. From the comparison, it is clear that Mauritius provides a more favourable environment for the establishment of a headquarter regime based on the ease of qualification as a headquarter company, the corporate tax rate is low to none and it has no CGT, dividends withholding tax, and interest withholding tax, transfer pricing and thin capitalisation, exchange control and finally CFC rules. The advantage that South Africa has is that of their double tax agreements with Nigeria and Algeria. The research paper also addresses the extent to which headquarter regimes in South Africa are considered to be treaty shopping. OECD Glossary of Tax Terms defines treaty shopping as: "An analysis of tax treaty provisions to structure an international transaction or operation so as to take advantage of a particular tax treaty. The term is normally applied to a situation where a person not resident of either the treaty countries establishes an entity in one of the treaty countries in order to obtain treaty benefits." 1 It further addresses the impact that treaty shopping has on our general anti - avoidance legislation. Research paper 2 (Local tax) Is customer loyalty programmes capital or revenue of nature? The general gross income definition is defined as '... the total amount, in cash or otherwise, received by or accrued to in favour of such resident during such year or period of assessment, excluding receipts or accruals of a capital nature...' The research problem is extracted from the general gross income definition. The research problem is based on the fourth element of the general gross income definition, namely, whether the transaction is of revenue or a capital nature. In formulating an answer to our research problem, being the last element of the general gross income definition, we look at case law handling the test applied by courts on revenue versus capital applications. The test laid down, deals with the intention, duration, nature and frequency of the customer loyalty programme being of a revenue or capital nature. In terms of the general gross income definition, all elements except the last element, being, the transaction must be of a capital nature, are met. As all the elements of the general gross income definition are not met, the rewards from a customer loyalty programme should not be taxable in the hands of th e customer. However, capital gains tax consequences can be dealt with as the reward received as part of the customer loyalty programme is of a capital nature. If for some reason, SARS proves that a customer embarked in a customer loyalty programme as part of a scheme to make profits and therefore he should be taxed on the reward, the onus SARS having to collect monies from taxpayers would far exceed the monies received. And in most cases, majority of the active users of a customer loyalty programme would be below the submission of tax return threshold. With this said, we are assuming that due to the changes in economic climate the majority of the users would be from a low income background.